THE EFFECT OF RESISTANCE EXERCISE ON QUALITY OF LIFE AND SYMPTOMS OF DEPRESSION IN THE ELDERLY. (Fiep Bulletin - online, 2012)
Data indicate the global aging population. This phase of life is characterized as a process of cognitive and functional losses. This growth accompanied by a high rate of chronic degenerative diseases, among them those that affect the central nervous system, especially depression, which is a "disease" diagnosed from the symptoms that manifest a certain duration, frequency and intensity. Considered today as the most important for the elderly, resistance exercise (RE) wins a major role because of the high degree of security and its stimuli to cardiovascular health and psychological. In this context, this study aims to determine what the effects of ER in depressive symptoms and quality of life in older adults 60 to 80 years of Project ER and Quality of Life you read. Data were collected through questionnaires SF-36 and Yesavage Geriatric Scale (1983). This research was conducted at the read through, with a sample of 30 elderly volunteers of both sexes, which are divided into two groups: experimental group (EG) and Control Group (CG) of 15 elderly. We used descriptive statistics to present the frequency distribution data of different classifications of depression. For the inferential statistics we used the Student t test and chi-square test to analyze the difference between the levels of classification of intra-depression group. To analyze the inference was adopted a significance level of p ? 0.05. It was observed that there was a statistically significant difference between groups, with advantage for GE, which had better quality of life index and no depression. It is concluded that the practice of ER, appears to favor the lower levels of depression and improve quality of life indices.
Keywords: Elderly; Strength Training; Depressive Symptoms